2011
DOI: 10.1097/opx.0b013e3182279ff8
|View full text |Cite
|
Sign up to set email alerts
|

Placido-Based Indices of Corneal Irregularity

Abstract: All the primary indices proposed in this work exhibit very good performance in discriminating between normal and irregular corneas. The accuracy of the combined indices is optimal within the test group (perfect classification), allowing their use in clinical practice as corneal markers of a disease. All these indices are fast to compute and can be easily implemented in any corneal topography system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…7,8,[59][60][61][62][63] The digital analysis of the image of the Placido disks projected on the cornea has also been shown to be a valid tool for keratoconus diagnosis, avoiding the use of estimated data or parameters obtained indirectly. 64 Specifically, the use of primary corneal indices characterizing the asymmetry of the mires seems to be especially useful for keratoconus detection. 64 …”
Section: Screening Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,[59][60][61][62][63] The digital analysis of the image of the Placido disks projected on the cornea has also been shown to be a valid tool for keratoconus diagnosis, avoiding the use of estimated data or parameters obtained indirectly. 64 Specifically, the use of primary corneal indices characterizing the asymmetry of the mires seems to be especially useful for keratoconus detection. 64 …”
Section: Screening Systemsmentioning
confidence: 99%
“…64 Specifically, the use of primary corneal indices characterizing the asymmetry of the mires seems to be especially useful for keratoconus detection. 64 …”
Section: Screening Systemsmentioning
confidence: 99%
“…More specifically, in the field of ophthalmology, there are several studies that use CAD methods to develop the concept of a patient-specific model [16][17][18][19][20]. These patient-specific models are obtained from the so called "raw data" [21], which are generated by systems based on the projection of a slit of light onto the cornea and on the principle of the Scheimpflug photography [5]. These raw data are not interpolated and are used to generate a geometric model with the modal methods called Zernike polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…These Zernike polynomials are defined for all discrete points of the anterior and posterior corneal surfaces for their reconstruction. However, in cases of pathological corneas as, for instance, very aberrated corneas, it has been demonstrated that it is very difficult to define the Zernike polynomial order required to get the most relevant information about the corneal surfaces [21,22]. An alternative to these geometric models are the zonal methods called B-Spline functions [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation